Teacher profile in medical undergraduate training in Piauí (Research, Society and Development, 2021)
The study aimed to analyze the profile of professors in medical graduation training in Piauí, considering the growing number of vacancies for admission to the course. Based on the information available on the websites of the medical schools, the names of the professors were collected and, later, the profile was verified through the curriculum registered in the Lattes platform, of the National Council for Scientific and Technological Development (CNPq). To contemplate the analysis, the following information was analyzed: links and length of teaching experience, gender, education and academic qualifications. The information was organized in Excel spreadsheets. Of the 315 curricula accessed, 140 teachers are female and 175 male. With regard to academic training, 211 are doctors, 89 from other training, 15 had no record. Regarding academic degrees, 123 are doctors, 77 are masters, 95 are specialists, 4 are post-docs and 16 are unregistered. Regarding teaching time, we found that there were teachers with 10 years of teaching, 1 and 5 years, 5 to 10 years of teaching and professionals with up to 1 year of experience in the classroom, some of which are not available. In employment relationships, professionals with 1 and 3 jobs, 4 and 6 jobs, more than 6 jobs, others without records were obtained. Through the analysis of the professors' profile, it was possible to draw an overview for the identification of weaknesses in the process of medical training in Piauí, so that it is possible to resolve them and graduate doctors with the profile that is recommended by the Diretrizes Nacionais Curriculares.